Colleges and schools-Lyles College of Engineering-Civil Engineering 014
Dr. Fareed Nader (standing Left), associate professor of engineering at CSU, Fresno, explains the operation of a stereoplotter to surveying the photogrammetry majors Jean Chau (right) of Los Angeles and Chris Murphy (seated) of Mill Valley. The device traces land contours from aerial photographs.